Gas and particle phase data of NOx effect on α-pinene SOA under low and high HO2/RO2 ratios - Geretti, Veronica; Hallquist, Mattias (University of Gothenburg, 2026)
The shared datasets report the utilized data to plot figure,1,2,3,4 and S1. The data is about about Secondary Organic Aerosol (SOA) formation from α-pinene photooxidation under two chemical regimes: under a low HO2-to-RO2 ratio to represent a typical chamber experiment and under a high HO2-to-RO2 ratio to represent more atmospherically relevant conditions.

De delade datamängderna rapporterar de använda data för att plotta figur 1, 2, 3 och 4 samt S1. Data handlar om bildandet av sekundär organisk aerosol (SOA) från α-pinen-fotooxidation under två kemiska regimer: under ett lågt HO2-till-RO2-förhållande för att representera ett typiskt kammarexperiment och under ett högt HO2-till-RO2-förhållande för att representera mer atmosfäriskt relevanta förhållanden.
Gas- och partikelfasdata för NOx-effekt på α-pinen SOA under låga och höga HO2/RO2-förhållanden
Keywords: Secondary organic aerosol; Sekundär organisk aerosol; Hydroperoxy Radicals; Hydroperoxiradikaler; nitrogen oxides; kväveoxider; Peroxy radicals; Peroxiradikaler; Other Chemistry Topics; Annan kemi